2020
DOI: 10.1186/s12890-020-1083-4
|View full text |Cite
|
Sign up to set email alerts
|

The association of delta neutrophil index with the prognosis of acute exacerbation of chronic obstructive pulmonary disease

Abstract: Background: Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) is associated with infective triggers including bacterial or viral in many cases, and pneumonia is a major contributor to hospitalization for AECOPD and has a close relationship with poor outcomes. Increased delta neutrophil index (DNI) can be useful in the detection of COPD patients with pneumonia. Methods: A retrospective cohort study was performed to investigate the mortality rate of the patients who were re-admitted within 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This suggests that DNI could be a more effective predictor of the level of systemic inflammation than procalcitonin. Park et al compared the prognostic and predictive values of DNI and procalcitonin biomarkers with ROC curve analysis and determined that the diagnostic accuracy of DNI was better [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that DNI could be a more effective predictor of the level of systemic inflammation than procalcitonin. Park et al compared the prognostic and predictive values of DNI and procalcitonin biomarkers with ROC curve analysis and determined that the diagnostic accuracy of DNI was better [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…11,16 DNI values were also validated in several lower respiratory diseases such as chronic obstructive pulmonary disease, pulmonary tuberculosis, and community-acquired pneumonia. 16,28,29 Meanwhile, Kang et al 12 reported that the DNI cut-off level for deciding to proceed with emergent surgery in acute diverticulitis is .7%. A combination of DNI and CT imaging could provide optimal diagnostic precision in patients with acute diverticulitis who visit the emergency department.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with acute PTE, 1-to 3-month mortality rates range between 5.4-15% and these rates may reach up to 50% in the presence of hypotensive shock (10). Repeated acute exacerbations of COPD lead to reduced lung function as well as repeated hospitalization, and increased mortality and morbidity (11). In-hospital mortality rate has been reported as 6.7% while shortterm mortality rates vary between 1.8% and 20.4% (12).…”
Section: Discussionmentioning
confidence: 99%